STUDENT HEALTH INSURANCE; ISLAMIC LAW STUDY ON THE MANAGEMENT MODEL OF HEALTH INSURANCE IN ISLAMIC BOARDING SCHOOLS (PONDOK PESANTREN) - Ainul Yaqin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
Health insurance is a right for every citizen, including students in Islamic boarding schools (pondok pesantren). Pondok pesantren has a unique independent way of providing health insurance for its residents. Several pesantrens that are the location of this research run a model of student health insurance which is managed by the board with a mechanism similar to the insurance mechanism. This study aims to explore how the model of health insurance is run in Islamic boarding schools and a review of Islamic law on the health insurance. This research is a field research conducted with a normative-sociological approach. The data sources for this research are the health insurance managers in two Islamic boarding schools, namely Pondok Pesantren Krapyak, Yogyakarta and Pondok Pesantren Darussalam, Purwokerto. These data were obtained through observation, interviews, and documentation. The results of this study are that the santri health insurance model in the two pesantrens is run with a similar mechanism of insurance in which the students pay regular fees to the management. When students (santri) get sick, they can get treatment at the pesantren health facility for free. The difference is in the management of funds where at the Pondok Pesantren Krapyak, the funds are managed by the foundation's management and the clinic will submit a claim every month. Meanwhile, at Pondok Pesantren Darussalam, the management of funds and health services is managed simultaneously by the Poskestren management. In a review of Islamic law, the contract in the guarantee is in line with the provisions of Islamic law. The contribution from students (santri) can be considered as tabarru’ funds in the form of grants or alms which are intended to help and bear each other. Contribution funds that have been collected are also managed in a way that does not conflict with the sharia.